Organisational perceptions of adapting to a changing climate - Denyse S. Dookie; Declan Conway; Suraje Dessai; Evan Oliner (Climate Risk Management, 2024)
Organisations, in the private, public and third sectors, are critical stakeholders and actors in the governance of climate change adaptation. Understanding organisational perceptions of preparedness, risk and response to climate change is important for effective climate adaptation-focused actions and policy design. Our study focuses on two research questions: what factors influence adaptation actions by organisations?, and what do organisations mean by the term ‘adaptation’? To address these, we developed and analysed a national survey of UK-based organisations’ perceptions of adapting to a changing climate, administered in spring 2021 (n = 2,429). Our findings confirm that awareness matters: respondents who reported that their organisation had high levels of concern about climate change risk or threat, and which had greater integration of adaptation within processes, are more likely to take adaptation action. In addition, we find a positive relationship between the occurrence and type of extreme event experienced and increased adaptation action by organisations. However, when asked about specific adaptation measures taken by organisations, examples of mitigation are more frequently mentioned compared to adaptation-type actions. Whether this may signal confusion or conflation of adaptation and mitigation by organisations requires further study. These findings offer critical insights into the perceptions of organisations as pivotal leaders of enacting responses to climate change. A renewed focus on organisational experiences, awareness, attitudes and capacity regarding adaptation can assist in better understanding how organisations can facilitate improved climate-resilient decision-making.